2016
DOI: 10.1002/ajmg.a.37883
|View full text |Cite
|
Sign up to set email alerts
|

Gene variants as risk factors for gastroschisis

Abstract: In a population‐based case‐control study in California of 228 infants, we investigated 75 genetic variants in 20 genes and risk of gastroschisis with regard to maternal age, race/ethnicity, vitamin use, and smoking exposure. We hypothesized that genes related to vascular compromise may interact with environmental factors to affect the risk of gastroschisis. Haplotypes were constructed for 75 gene variants using the HaploView program. Risk for gastroschisis associated with each gene variant was calculated for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
(34 reference statements)
0
15
1
Order By: Relevance
“…22 Previous reports revealed the effect of ICAM1 polymorphism on gastroschisis. 4,5 However, our study was unable to show an association between ICAM1 K469E polymorphism and gastroschisis risk, implying that the gastroschisis pathogenesis might be affected by several genetic risks, not only ICAM1 K469E variant. Furthermore, it seems likely that the gene-environment interaction has more impact on gastroschisis pathogenesis than a single genetic etiology.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…22 Previous reports revealed the effect of ICAM1 polymorphism on gastroschisis. 4,5 However, our study was unable to show an association between ICAM1 K469E polymorphism and gastroschisis risk, implying that the gastroschisis pathogenesis might be affected by several genetic risks, not only ICAM1 K469E variant. Furthermore, it seems likely that the gene-environment interaction has more impact on gastroschisis pathogenesis than a single genetic etiology.…”
Section: Discussioncontrasting
confidence: 60%
“…3 Recently, several studies have demonstrated an association between gastroschisis risk and common variants of the cell-cell interaction gene intracellular adhesion molecule 1 (ICAM1). 4,5 So far, there have been no such reports from the Asian region. Therefore, an additional study is warranted in Asia, particularly in Indonesia, because the ICAM1 K469E polymorphism frequency differs among ethnic groups, 6 and its effect on gastroschisis has never been determined to date.…”
mentioning
confidence: 99%
“…Unique to Utah, multigenerational pedigrees provide a rare opportunity to discover disease risk variants for any condition, including gastroschisis. Others have investigated specific gene variants based on known risk factors or animal studies of gastroschisis (Cardonick et al, ; Feldkamp, Bowles, & Botto, ; Jenkins et al, ; Padula et al, ; Torfs, Christianson, Iovannisci, Shaw, & Lammer, ). Padula et al () recently reported statistically significant associations with genes involved in cell–cell interactions ( ICAM1 , ICAM4 , ICAM5 ) and blood pressure ( NOS3 , ADD1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also maternal exposure to environmental factors, such as smoking during pregnancy as well as vitamin use, in white and Hispanic mothers of different age groups has been studied. The result of this study was that a few gene variants may be associated with a higher risk for gastroschisis, but further studies are needed (Padula et al, ).…”
Section: Discussionmentioning
confidence: 88%